2012
DOI: 10.1590/s0073-47212012000300009
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of Conepatus chinga (Carnivora, Mephitidae) and other medium-sized mammals in grasslands of southern Brazil

Abstract: ABSTRACT. Between January 2007 and December 2010, the abundance of medium-sized mammals was studied, with special focus on the Molina's hog-nosed skunk, Conepatus chinga (Molina, 1782), at four locations in southern Brazil. In this study, transect line methodology was used to obtain data for Distance Analyses. Transects were traveled by car at night, searching with spotlights along the edges of secondary roads in agricultural landscapes. Along 1,811 km, we obtained 620 observations of 20 mammal species. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
2
7
1
Order By: Relevance
“…Similarly, Zapata et al (2005) found a diet based on rodents (56% of biomass) and lagomorphs (34.5%) from the southern limit of the species' distribution, while Ebensperger et al (1991) described G. cuja as preying on rabbits, rodents, and small marsupials in central Chile. However, in our study, we found no evidence that the grison consumed lagomorphs, despite the high abundance of Lepus europaeus (Pallas, 1778) in some parts of Rio Grande do Sul (Kasper et al 2012a).…”
Section: Discussioncontrasting
confidence: 93%
“…Similarly, Zapata et al (2005) found a diet based on rodents (56% of biomass) and lagomorphs (34.5%) from the southern limit of the species' distribution, while Ebensperger et al (1991) described G. cuja as preying on rabbits, rodents, and small marsupials in central Chile. However, in our study, we found no evidence that the grison consumed lagomorphs, despite the high abundance of Lepus europaeus (Pallas, 1778) in some parts of Rio Grande do Sul (Kasper et al 2012a).…”
Section: Discussioncontrasting
confidence: 93%
“…Our estimates are more than double the largest previously estimated home range for the species, also using MCP, wbereby Sunquist et al (1989) determined the bome range area of tbeir subjects in the Venezuelan llanos to be 0.18 km^ in the wet season and 0.54 km^ in the dry season. There is little information available regarding the home ranges of other Mepbitid species in South American, aside from a few area estimates ranging from 1.95 to 0.55 km^ for C. chinga (Donadio et al, 2001;Reppucci et al, 2009;Kasper et al, 2012a) and 0.09 to 0.16 km^ for C. Humboldt (Fuller et al, 1987;Johnson et al, 1988), which are summarized in table 2. Different methods, different ecological requirements of each species, tbe relative abundance of Sunquist et al,, 1989 This study Kasperetal,, 2012bKasper et al, 2012bReppucci et al,, 2009Donadio et al,, 2001Fuller et al, 1987Fuller et al, 1987Fuller et al, 1987Johnson et al, 1988Johnson et al, 1988Johnson et al, 1988 Juvenile.…”
Section: Home Rangementioning
confidence: 99%
“…In North America, other species of the skunk Family Mephitidae have received greater attention because some of them may be vectors for rabies (WadeSmith & Verts, 1982), and in some rare instances cause crop damage (Olson & Lewis, 1999), while other species have shown dramatic population declines (Gompper & Hackett, 2005). For species occurring in South America, data on activity patterns, home range and habitat use (Donadio et al, 2001;Kasper et al, 2009;Reppucci et al, 2009;Kasper et al, 2012b), diet (Travaini et al, 1998;Donadio et al, 2004;Montalvo et al, 2008), and abundance (Kasper et al, 2012a) have been collected for C. chinga. Also, Johnson et al (1988) discussed the influence of seasonal changes on the activity patterns of C. humboldti and assessed the home range area of this species in Chile.…”
Section: Introductionmentioning
confidence: 99%
“…There are records of the species using forest (CHEREM et al, 2004;CHEREM, 2005;KASPER et al, 2012), showing the huge impact of roads on wildlife.…”
Section: Discussionmentioning
confidence: 99%